PELATIHAN PEMBUATAN GUMMY CANDY (YUPI) DARI BUAH ASLI DI DESA WANAJAYA - Fitriya, Ayu; Budianti, Yudi; Rikmasari, Rima (Universitas Islam 45 Bekasi, 2025)
Stunting in toddlers is a significant health problem in Indonesia, with a prevalence reaching 24.4% in 2021. Although in Wanajaya Village, stunting cases have been successfully reduced to 0%, the problem of malnutrition in children is still common. Good nutritional status is very important for the growth and development of children, especially toddlers, who need a balanced nutritional intake. One solution to increase children's nutritional intake is to utilize fruits as part of their daily diet. However, children often prefer sweet foods to fresh fruit. This study aims to introduce the manufacture of gummy candy from real fruit juice as an alternative healthy snack that can increase fruit consumption in children. By replacing sugar with honey, this gummy candy provides nutritional benefits without damaging dental health or triggering sugar addiction. The training held in Wanajaya Village aims to increase parental awareness of the importance of fruit consumption and provide skills in making healthy snacks. It is hoped that this training can help parents in overcoming children's nutritional problems and encourage better fruit consumption.